A behaviour‐based coding tool for assessing supervisors' adherence and competence: Findings from a motivational interviewing implementation study. (29th June 2022) - Beckman, Maria; Alfonsson, Sven; Rosendahl, Ingvar; Berman, Anne H.; Lindqvist, Helena
Abstract: Supervision seems to be an essential part of therapist training and thus also of implementing evidence‐based practices. However, there is a shortage of valid and reliable instruments for objective assessment of supervision competence that include both global measures and frequency counts of behaviour—two essential aspects of supervisory competence. This study tests the internal consistency and inter‐rater reliability of an assessment tool that includes both these measures. Additionally, strategies and techniques used by 10 supervisors in 35 Motivational interviewing supervision sessions are described. Codings were conducted after two separate coding training sessions. The internal consistency across the global measures was acceptable ( α = 0.70; 0.71). After the second training, the inter‐rater reliabilities for all frequency counts were in the moderate to good range, except for two that were in the poor range; inter‐rater reliability for one of the four global measures was in the moderate range, and three were in the poor range. A prerequisite for identifying specific supervisor skills central to the development of therapist skills, teaching these skills to supervisors and performing quality assurance of supervision, is to create instruments that can measure these behaviours. This study is a step in that direction.